Toll-Like Receptor 4 Expression on Lymphoma Cells Is Critical for Therapeutic Activity of Intratumoral Therapy With Synthetic TLR4 Agonist Glucopyranosyl Lipid A - Lu, Hailing; Betancur, Alec; Chen, Michael; ter Meulen, Jan H. (Frontiers in Oncology, 2020)
Intratumoral (IT) injections of Glucopyranosyl lipid A (G100), a synthetic toll-like receptor 4 (TLR4) agonist formulated in a stable emulsion, resulted in T-cell inflammation of the tumor microenvironment, systemic tumor-specific CD4 and CD8 T-cell responses, and complete cure of mice with large established A20 lymphomas, including cure of 50% of animals in a bilateral tumor model in which only one lesion was injected. Surviving mice resisted a secondary challenge and depletion of CD8 T-cells, but not CD4 or NK cells, abrogated the anti-tumor effect. Unexpectedly, TLR4 knock-out in A20 cells rendered tumors completely non-responsive to G100. As shown by genotyping and phenotyping analysis, G100 strongly activated antigen presentation functions in A20 cells in vitro and in vivo and induced their apoptosis in a dose dependent manner. Similarly, the TLR4 positive human mantle cell lymphoma line Mino showed in vitro activation with G100 that was blocked with an anti-TLR4 antibody. In the A20 model, direct activation of immune functions in B-lymphoma cells with G100 is sufficient to induce protective anti-tumor CD8 T-cell responses and TLR4 expressing human B-cell lymphomas may be amenable to this therapy as well.